PENERAPAN MODEL SADHARANIKARAN DALAM RETORIKA POLITIK MODERN DI ERA GLOBALISASI - Suarjaya, I Nyoman Alit; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
In this era of globalization, the development of Asian communications has begun to show an increasingly open dynamic. This article seeks to explore the application of the Asian communication model in modern political rhetoric and its implications for relations development. Asian-based communication requires continuous study. The diverse social and cultural dynamics that are based on the culture of selfishness are not yet fully understood only on the basis of Western communication theory. This article seeks to explain the advantages of a "culture-based" communication model that can develop meaningful relationships in the context of modern political rhetoric by building strong and empathic relationships, enhancing the effectiveness of messages, reducing polarization, and enhancing constructive dialogue.